Increasing Intrapersonal and Interpersonal Intelligence Through Implementation of Problem Posing - Firmansyah, Eka; Saniah, Lia; Rachmalia, Nela; Yaniawati, R. Poppy; Dwiyana, A. Sy. Dina (Kreano, Jurnal Matematika Kreatif-Inovatif, 2024)
This Classroom Action Research (CAR) is an effort to improve students' intrapersonal and interpersonal intelligence through the application of Problem Posing in mathematics learning in Junior High Schools on Constructed Spaces with Curved Sides. The research subjects were 64 students from the 9th grade of a Junior High School in Bandung. Data collection techniques include interviews, questionnaires, observations, and documentation. Intrapersonal and interpersonal intelligence in the experimental class using the Problem Posing learning model is relatively better than the control class using conventional learning models. The results of this study show that the application of the Problem Posing learning model can improve students' intrapersonal intelligence and interpersonal intelligence. There are several advantages that researchers get in implementing Problem Posing besides students become the center of learning and practice working in groups, students become much more enthusiastic so that the learning atmosphere is conducive and full of activity, and presentation activities can build courage and confidence in performance. Learning performance and building a positive attitude during learning. Suggestion: The problem-posing learning model can be an alternative to be applied in the classroom because it can foster self-confidence and make students more active, thereby increasing students' mathematical communication skills, which correlate with interpersonal intelligence. Penelitian ini sebagai upaya untuk meningkatkan kecerdasan intrapersonal dan interpersonal siswa melalui penerapan Problem Posing pada pembelajaran matematika di Sekolah Menengah Pertama (SMP) pada materi Bangun Ruang Sisi Lengkung. Jenis penelitian yaitu Penelitian Tindakan Kelas (PTK). Subyek penelitian sebanyak 64 orang siswa kelas 9 salah satu SMPN di Bandung. Teknik pengumpulan data meliputi: wawancara, angket, observasi, dan dokumentasi. Kecerdasan intrapersonal dan interpersonal pada kelas eksperimen dengan penggunaan model pembelajaran Problem Posing, relatif lebih baik dari kelas kontrol yang menggunakan model pembelajaran konvensional. Hasil dari penelitian ini bahwa penerapan model pembelajaran Problem Posing dapat meningkatkan kecerdasan intrapersonal dan kecerdasan interpersonal siswa, terbukti dari peningkatan rata-rata keduanya pada setiap siklus. Ada beberapa kelebihan yang didapat peneliti dalam menerapkan Problem Posing, selain siswa menjadi sentral pembelajaran dan melatih bekerja dalam kelompok, siswa menjadi jauh lebih semangat dan antusias sehingga suasana pembelajaran kondusif dan penuh aktifitas, selain itu kegiatan presentasi dapat membangun keberanian dan keyakinan dalam unjuk kinerja belajar dan membangun sikap positif selama pembelajaran. Oleh karena itu, model pembelajaran Problem Posing dapat menjadi alternatif untuk di-terapkan di dalam kelas karena dapat menumbuhkan percaya diri siswa untuk lebih aktif sehingga mampu meningkatkan kecerdasan intrapersonal dan kecerdasan interpersonal.